Interactions between Personality, Depression, Anxiety and Cognition to Understand Early Stage of Alzheimer’s Disease - Zufferey, Valérie; Gunten, Armin v.; Kherif, Ferath (Current Topics in Medicinal Chemistry, 2020)
The multifaceted nature of Alzheimer’s disease (AD) and Mild cognitive impairment (MCI) can lead to wide inter-individual differences in disease manifestation in terms of brain pathology and cognition. The lack of understanding of phenotypic diversity in AD arises from a difficulty in understanding the integration of different levels of network organization (i.e. genes, neurons, synapses, anatomical regions, functions) and in inclusion of other information such as neuropsychiatric characteristics, personal history, information regarding general health or subjective cognitive complaints in a coherent model. Non-cognitive factors, such as personality traits and behavioral and psychiatric symptoms, can be informative markers of early disease stage. It is known that personality can affect cognition and behavioral symptoms. The aim of the paper is to review the different types of interactions existing between personality, depression/anxiety, and cognition and cognitive disorders at behavioral and brain/genetic levels.
Keywords: Neurobiology